The Training Of Public, Health Personnel And School Counselors To Help Tsunami Survlvors: Malaysian Experience. - See, Assoc. Prof. Dr., Ching Mey (2005)
The disaster Tsunami struck on 26tt1 December 2004 and its' devastating effects were concentrated at the northern coastal areas of Penang, an island in Malaysia. The number of deaths currently stands at 68 with 52 in Penang, 12 in Kedah, 3 in Perak and 1 in Selangor. Many families were traumatized by the experience.